The Influence of Audio Visual Media on the Science Learning Outcomes of Class V Students of State Elementary School 095552 Jl. Asahan - Hematryn Ompusunggu; Muktar B Panjaitan; Selamat Triadil Saragih (MultiTech Publisher, 2023)
Based on the results of observations that have been seen during the PPL period in this school, the results show that teachers very rarely use teaching aids or learning media in teaching in the classroom so that students become less active in following the lessons given by the teacher, so that learning outcomes which was achieved by fifth grade students It is still considered beautiful because it has not yet reached the Minimum Completeness Criteria (KKM) value. The type of research used in this research is quantitative, the population of this research is all class V students at SD Negeri 095552 Jl.Asahan totaling 26 students. Saturated sampling technique, the sample in this study consisted of all class V of SD N 095552 Jl. Asahan, totaling 26 students. The research results show that student learning outcomes using audio-visual media are in the good category. The results of the t distribution test at a significant level (α = 0.05) dk = N–1=26-1=25, namely tcount > ttable, then the t distribution data with the result is 39.442> 2.060, so it can be said that there is a significant influence. The results and table of the t test prove that there is an influence of audio visual media (X) on learning outcomes (Y) with the results rcount > rtable with the results tcount > ttable 39.442> 2.060, so Ho is rejected and Ha is accepted.